Sigmund Freud analysis of the mind - Schipper, Henry (A&E Televsion Networks, 1995)
His revolutionary ideas transformed our conception of the mind. Yet the father of psychoanalysis was plagued by neurotic fears and troubling obsessions. Freud is arguably the most influential thinker of modern times. His theories continue to inspire discovery and debate. Revisit the life of the man who was once derided as the 'Doctor of Love'.From the childhood that inspired many of his radical ideas to his eventual worldwide fame, this program explores the details of Freud's life, including his obsessive behavior and dangerous bouts with addiction.